Work or personal life – a piece on modern consumer’s problems with managing the time budget - Burlita, Augustyna; Błoński, Krzysztof (Economic and Environmental Studies, 2020)
In the state of huge time compression that is characteristic of the modern consumer life, it is getting increasingly harder to meet all the challenges and fulfil all the tasks that we would like to or should undertake. Taking into consideration the relentlessness and inflexibility of time as well as its limited resources and simultaneously the ever increasing number of activities that occupy a space in a human time budget, the ability to manage one’s time, including especially balancing its budget, is currently gaining a special importance. For it is a significant precondition for a person’s balanced development as an employee, a member of a family or another group but also as an individual with specified needs, preferences and value system. The aim of this publication is to describe the problems of modern consumers – inhabitants of big cities, with managing the time budget, especially with regard to the possibility of maintaining a time balance between the different areas of life. The considerations were based both on the study of scientific literature, as well primary research conducted by the authors